Sick building syndrome among office workers in relation to office environment and indoor air pollutant at an academic institution, Malaysia - Zainal, Zarith Afzan; Hashim, Zailina; Jalaludin, Juliana; Lim, Fang Lee; Hashim, Jamal Hisham (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Good indoor air quality (IAQ) is important for workers’ well-being whilst simultaneously optimize work productivity and job performance of the workers in an office. This study aims to determine the association between the sick building syndrome (SBS) in relation to the personal factors, indoor office environment and indoor air pollutants at an academic institution in Malaysia. Methods: A total of 342 office workers; made up of 188 (55%) female and 154 male (45%), from 14 different office buildings; made up of administrative, faculties, centers, institutes and school, participated in this study. A self-administered questionnaire was used to determine symptoms related to SBS. Real time readings of IAQ parameters were conducted three times daily for 15 minutes /sampling point. Results: Results showed higher prevalence of the SBS symptoms generally among women; diagnosed asthma was positively associated with mucosal symptoms; current smoking was significantly associated with skin symptoms; and centralized air conditioning system, the use of photocopiers, printers or fax machines for more than 1 hour per day and installation of a new carpet in the office environment were significant risk factors of SBS. After adjusting for demographic characteristics, formaldehyde, ultrafine particle and total volatile organic compounds were significantly associated with mucosal symptoms. Conclusion: Demographic characteristics, indoor office environment and indoor air pollutants were significant risk factors of SBS among workers in this study. It is highly recommended to maintain good housekeeping and to isolate printers and photocopier machines from the main workplace since both were sources of particulates.